2010
DOI: 10.1007/978-3-642-16644-0_59
|View full text |Cite
|
Sign up to set email alerts
|

Robust Wireless Network Coding – An Overview

Abstract: Abstract. Network Coding (NC) has witnessed a tremendous upsurge in interest and activities in recent years, both in academia and industry. Indeed, since the pioneering publication of Ahlswede et al. in 2000, NC has rapidly emerged as a major research area in information theory due to its wide applicability to communication through real networks. The many contributions available in the literature to date, ranging from purely theoretical studies on fundamental limits to practical experimentations in real-world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…We consider a very simple implementation in which the relays demodulate-network-code-and-forward (D-NC-F) each received symbol without checking whether the symbol is correct or wrong. The main aim of this assumption is to keep the complexity of the relays at a very low level (Koetter & Kschischang, 2008), and to understand the robustness, in terms of coding and diversity gain, of the error propagation problem (Di Renzo et al, 2010a), (Di Renzo et al, 2010b) on various network codes.…”
Section: Xymentioning
confidence: 99%
“…We consider a very simple implementation in which the relays demodulate-network-code-and-forward (D-NC-F) each received symbol without checking whether the symbol is correct or wrong. The main aim of this assumption is to keep the complexity of the relays at a very low level (Koetter & Kschischang, 2008), and to understand the robustness, in terms of coding and diversity gain, of the error propagation problem (Di Renzo et al, 2010a), (Di Renzo et al, 2010b) on various network codes.…”
Section: Xymentioning
confidence: 99%
“…NC offers the promise of improved performance over state-of-the-art routing, and, in particular, it finds successful application in multi-hop/cooperative wireless networks [2], [3], as it offers an efficient way for boosting the achievable throughput (see [4], [5], and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we consider Rayleigh fading assumption for all links for convenience. In order to avoid mutual interference, we consider that transmissions are scheduled in time-orthogonal timeslots [4]. We study both perfect CSI and imperfect CSI at the receiver.…”
Section: System Modelmentioning
confidence: 99%
“…Recent results have shown that NC can also provide improved performance and energy efficiency compared with conventional network routing techniques [4]. However, besides the many potential advantages and applications of NC over classical routing, the NC principle is not without limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation